2018
DOI: 10.1016/j.ijhydene.2017.11.150
|View full text |Cite
|
Sign up to set email alerts
|

Interface stability between bare, Mn Co spinel coated AISI 441 stainless steel and a diopside-based glass-ceramic sealant

Abstract: Interface stability between bare, Mn-Co spinel coated AISA 441 stainless steel and a diopside-based glassceramic sealant',

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…The addition of ZnO decreases the electrical resistance, which enhanced a higher degree of corrosion in the steel/Crofer22 APU interconnect, which could lead to a short circuit. Hence, the MgO‐containing glass was considered to be a more useful candidate as a SOFC sealant due to its greater stability, in the dual atmosphere, lower level of corrosion at H 2 side, and lower conductivity in air 207 . Sabato et al 21 have reported the interaction study between the diopside‐based glass‐ceramics with AISI441 interconnect materials.…”
Section: Effect Of Different Glass Constituents On Sealing Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of ZnO decreases the electrical resistance, which enhanced a higher degree of corrosion in the steel/Crofer22 APU interconnect, which could lead to a short circuit. Hence, the MgO‐containing glass was considered to be a more useful candidate as a SOFC sealant due to its greater stability, in the dual atmosphere, lower level of corrosion at H 2 side, and lower conductivity in air 207 . Sabato et al 21 have reported the interaction study between the diopside‐based glass‐ceramics with AISI441 interconnect materials.…”
Section: Effect Of Different Glass Constituents On Sealing Propertiesmentioning
confidence: 99%
“…Hence, the MgO-containing glass was considered to be a more useful candidate as a SOFC sealant due to its greater stability, in the dual atmosphere, lower level of corrosion at H 2 side, and lower conductivity in air. 207 Sabato et al 21 have reported the interaction study between the diopsidebased glass-ceramics with AISI441 interconnect materials. They formed the hermitic sealant even after very long durations $3500 hours.…”
mentioning
confidence: 99%
“…The study and then the use of commercial FSSs as base material for IC in IT-SOFCs stacks is not a novelty, as it is represented by the case of FSSs AISI 441 and AISI 444 [37][38][39][40][41][42]. Since the manufacture of MIC represents about 45% of the overall stack production costs, the use of this group of FSSs can guarantee a reduction of those costs, even when further actions, e.g., the application of protective coatings, are needed [43].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies on alkali-containing diopside-based glass-ceramics sealants [20,22,44], it has been found that the strong heterogeneous nucleation of diopside, at the interface with the interconnect material may prevent detrimental reactions between the alkalis in the glassy phase and the Cr in the steel/oxide scale. However, to the authors best knowledge there are no papers focused on the testing of alkali-containing diopsidebased sealants under relevant conditions, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…300h. The glass-ceramic studied here was obtained by modifying a previous glass composition that had successfully survived periods longer than 1000h in a dual atmosphere or in air at 800°C, without the application of electrical voltage [22,44]. The changes in the compositions were tailored in order to increase the content of diopside in the glass-ceramic, which in turn led to a CTE value more suitable for its thermomechanical compatibility with Crofer22APU.…”
Section: Introductionmentioning
confidence: 99%